2019
DOI: 10.3389/fimmu.2019.01097
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in vivo Efficacy Assessment of Approved Orally Bioavailable Human Host Protein-Targeting Drugs With Broad Anti-influenza A Activity

Abstract: The high genetic variability of influenza A viruses poses a continual challenge to seasonal and pandemic vaccine development, leaving antiviral drugs as the first line of defense against antigenically different strains or new subtypes. As resistance against drugs targeting viral proteins emerges rapidly, we assessed the antiviral activity of already approved drugs that target cellular proteins involved in the viral life cycle and were orally bioavailable. Out of 15 candidate compounds, four were able to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Mast cells can intensify immunological injury through the production of mediators, including tryptase, TNF-α, IL-6, IL-1, and chemokine (C-C motif) ligand 3 (CCL3). Animal studies have shown that ketotifen can reduce excessive inflammation (cytokine storm), and ketotifen has been shown to reduce end organ damage and mortality in mice infected with H5N1 type Influenza A [ 42 ]. Ketotifen has been shown in mice infected with H5N1 influenza viral to dramatically reduce lung damage and mortality, even when the antiviral, oseltamivir, was dosed sub-optimally (ketotifen and oseltamivir 100% survival vs. oseltamivir alone 65%) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells can intensify immunological injury through the production of mediators, including tryptase, TNF-α, IL-6, IL-1, and chemokine (C-C motif) ligand 3 (CCL3). Animal studies have shown that ketotifen can reduce excessive inflammation (cytokine storm), and ketotifen has been shown to reduce end organ damage and mortality in mice infected with H5N1 type Influenza A [ 42 ]. Ketotifen has been shown in mice infected with H5N1 influenza viral to dramatically reduce lung damage and mortality, even when the antiviral, oseltamivir, was dosed sub-optimally (ketotifen and oseltamivir 100% survival vs. oseltamivir alone 65%) [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Broad-spectrum anti-paramyxovirus drug candidates that inhibit at least one family member with predictable disease burden in adults may offer a viable path to establish clinical proof-of-concept; provide benefit to a larger patient pool suffering from diverse paramyxovirus infections to better offset developmental costs; and widen windows of opportunity against at least some indications, since disease progression profiles vary between paramyxoviruses. However, traditional broad-spectrum antivirals are host-directed 14 19 or ribonucleoside analogs 20 23 that are unlikely to meet the tight safety profile necessary for pediatric use and therefore make poor anti-paramyxovirus candidates overall. Allosteric direct-acting antivirals are better suited to deliver the required safety margin, but are typically restricted to a single paramyxovirus target.…”
mentioning
confidence: 99%
“…More importantly, Theresa Enkirch et al [ 27 ] had evaluated the anti-influenza activity of dextromethorphan in vitro, and in mice as well as in animal models. The authors demonstrated that dextromethorphan was able to inhibit viral replication both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%